10-year trends in noncommunicable disease mortality in the Caribbean region - Hilda Razzaghi; Damali N. Martin; Sarah Quesnel-Crooks; Yuling Hong; Edward Gregg; Glennis Andall-Brereton; Vilma Gawryszweski; Mona Saraiya (Pan American Health Organization, 2019)
Objective. Between 2006 and 2016, 70% of all deaths worldwide were due to noncommunicable diseases (NCDs). NCDs kill nearly 40 million people a year globally, with almost three-quarters of NCD deaths occurring in low- and middle-income countries. The objective of this study was to assess mortality rates and trends due to deaths from NCDs in the Caribbean region. Methods. The study examines age-standardized mortality rates and 10-year trends due to death from cancer, heart disease, cerebrovascular disease, and diabetes in two territories of the United States of America (Puerto Rico and the U.S. Virgin Islands) and in 20 other English- or Dutch-speaking Caribbean countries or territories, for the most recent, available 10 years of data ranging from 1999 to 2014. For the analysis, the SEER*Stat and Joinpoint software packages were used. Results. These four NCDs accounted for 39% to 67% of all deaths in these 22 countries and territories, and more than half of the deaths in 17 of them. Heart disease accounted for higher percentages of deaths in most of the Caribbean countries and territories (13%-25%), followed by cancer (8%-25%), diabetes (4%-21%), and cerebrovascular disease (1%-13%). Age-standardized mortality rates due to cancer and heart disease were higher for males than for females, but there were no significant mortality trends in the region for any of the NCDs. Conclusions. The reasons for the high mortality of NCDs in these Caribbean countries and territories remain a critical public health issue that warrants further investigation.